2005
DOI: 10.3171/jns.2005.102.5.0856
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in outcome following sports-related concussion

Abstract: Return-to-play decisions and concussion management must be objective and made on an individual basis, including consideration of factors such as patient sex rather than relying on a one-size-fits-all guideline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
358
6
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 437 publications
(383 citation statements)
references
References 28 publications
15
358
6
4
Order By: Relevance
“…Another study found that juvenile males and females did not differ on a range of sensorimotor outcomes, which is consistent with our findings of motor‐related deficits in both male and female rats given RmTBI 67. Clinical studies of sex differences following mTBI in high school and collegiate students are currently conflicted; some have reported females are more likely to be cognitively impaired and experience more subjective and objective symptoms,11 while others have reported no differences in the number of symptoms, but sex differences in the type of symptoms experienced 64. Given the significant degree of brain maturation occurring during this critical period of development, sex‐dependent variations, and the differences in symptomology associated with single versus repetitive mTBI, it is not surprising that clinical studies have failed to produce reliable results regarding symptom presentation.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Another study found that juvenile males and females did not differ on a range of sensorimotor outcomes, which is consistent with our findings of motor‐related deficits in both male and female rats given RmTBI 67. Clinical studies of sex differences following mTBI in high school and collegiate students are currently conflicted; some have reported females are more likely to be cognitively impaired and experience more subjective and objective symptoms,11 while others have reported no differences in the number of symptoms, but sex differences in the type of symptoms experienced 64. Given the significant degree of brain maturation occurring during this critical period of development, sex‐dependent variations, and the differences in symptomology associated with single versus repetitive mTBI, it is not surprising that clinical studies have failed to produce reliable results regarding symptom presentation.…”
Section: Discussionsupporting
confidence: 89%
“…As males and females often report different PCS symptoms,11, 12 understanding whether or not underlying structural or epigenetic changes following mTBI and RmTBI contribute to these heterogeneous outcomes is an important undertaking. Owing to sex differences in brain maturation,7 an injury at a given age has the potential to affect the developmental trajectory of males and females in distinct ways.…”
Section: Introductionmentioning
confidence: 99%
“…While acute neuroprotective effects of oestrogen have been suggested in a rodent WD impact-acceleration model, 253 exacerbated outcomes following repeated mTBIs in female soccer players indicate complexities. 254 Finally, pediatric populations exhibit different responses to adults experiencing a similar head trauma, 255 and limited studies have been conducted assessing younger populations. 235,236,256,257 Conclusions Long-term cognitive impairments following CNS injury and in neurodegenerative diseases have been associated with prolonged oxidative stress conditions 131,258 and impaired signal conduction along dysmyelinated axons.…”
Section: Barriers To Clinical Translationmentioning
confidence: 99%
“…[19][20][21] Other research suggests that females may also be at higher risk of concussion and have slower recovery times. [22][23][24] Therefore, more aggressive prevention strategies may be indicated in these groups as well as among adult beginners.…”
Section: Discussionmentioning
confidence: 99%